Social media use for information-sharing activities among youth in Malaysia - Wok, Saodah; Syed Abdullah Idid, Syed Arabi; Misman, Norealyna (David Publishing Company, 2012)
Social media are popular among youth for sharing information. This study tries to explore the popularity of the social media sites, the level of use of the social media sites, the types of information-sharing activities involved on the social media sites, to compare youth of various background in relation to information-sharing activities, and to analyze the relationship between the level of social media use and the information-sharing activities among youth. This study employs a quantitative research design, using survey method with questionnaire as the research instrument used for data collection. In this study, youth aged between 17-40 years old nationwide were surveyed. The study was developed based on the user and gratification theory (Blumler & Katz, 1974). Findings showed that youth always (five to seven days per week) use social media to share information including personal information. Results also showed that youth used the social media more for sharing negatively-oriented information compared to the positively-oriented information. Although there were more items on the positively-oriented information-sharing activities but more youth spent their time on the negatively-oriented information-sharing activities. The results are supported by a strong relationship between frequency of use and the negatively-oriented information-sharing activities.